The Eyjafjalla eruption in 2010 and the volcanic impact on aviation - Weinzierl, Bernadett; Sailer, Thomas; Sauer, Daniel; Minikin, Andreas; Reitebuch, Oliver; Mayer, Bernhard; Schumann, Ulrich (Springer-Verlag Berlin Heidelberg, 2012)
This paper gives an overview of the Eyjafjallajökull (short: Eyjafjalla) eruption and its impact on aviation from the perspective of DLR research. The visual detectability of airborne volcanic ash at various distances from the volcano is discussed based on observations and simulations with a radiative transfer model. Ash loads above threshold conditions for safe aviation (2 mg m-3) as in spring 2010 should not be considered exceptional. A future research strategy to better prepare the aviation sector for future volcanic eruptions is outlined.